Pembentukan Nilai-Nilai Moral Pada Anak Usia Dini di RA Intan Permata Kecamatan Medan Marelan Pada Masa Pandemi Covid 19 - Ok. M. Daniel Syahindra; Andri Kurniawan; Mhd. Hafiz Arif Maulana Selian; Siti Hatizah; Mei Shita (AUD Cendekia, 2021)
This study aims to analyze the steps in inculcating moral values ​​in early childhood, the obstacles faced in inculcating early childhood moral values, and the cooperation of teachers and parents in inculcating early childhood moral values. This research was carried out at RA Intan Permata, Medan Marelan District. This study uses a qualitative research method based on descriptive studies with data collection techniques using interviews, observation and documentation studies. The results of the study indicate that there are several steps in inculcating AUD moral values, namely Moral Introduction, training on values ​​and morals through various activities both learning and outside learning, habituation of moral values ​​through example. There are several obstacles for teachers to instill moral values ​​in early childhood. Some of these barriers are internal and some are external. Internal means that it comes from the students themselves while external means that the obstacles come from outside the students themselves. With good cooperation between teachers and parents, of course, the cultivation of moral values ​​will be very easy to do, even by itself, moral values ​​will be formed as expected by teachers and parents.